SPLENIC RUPTURE DURING COLONOSCOPY: COMPLICATION OR MEDICAL ERROR? CASE REPORT AND MEDICO LEGAL IMPLICATIONS - Margherita Pallocci (Associazione Italiana Giovani Medici, 2021)
Iatrogenic splenic injury during colonoscopy is a rare but known occurrence. Such a rare event raises many issues relating to medical professional liability, since it is not always easy to establish whether the onset of the splenic injury is related to a technical error on part of the operator or simply to a complication. We report the case of a 52-year-old woman who, after undergoing a diagnostic therapeutic endoscopic procedure, suffered an acute spleen rupture, without documented bowel perforation, requiring emergency splenectomy. In the case herein reported, a further medico-legal issue is related to the failure of predicting such a complication, given its rare occurrence in the informed consent form signed by the patient.